2001
DOI: 10.1007/s002530000526
|View full text |Cite
|
Sign up to set email alerts
|

Two-step process for ketocarotenoid production by a green alga, Chlorococcum sp. strain MA-1

Abstract: The production of ketocarotenoids (KCs) from Chlorococcum sp. strain MA-1 was investigated by a two-step process. In the first step, 18 g biomass l(-1) was achieved by feeding glucose to the heterotrophic cultures; in the second step, the high-density cultures were treated with light illumination or chemical stress in dark, respectively, to induce KC synthesis. Light-treated cultures could produce 103 mg total KCs l(-1) and 32 mg astaxanthin l(-1), three times higher than those from chemical-treated cultures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Such a controlled switch that exploits the advantages of both autotrophy and heterotrophy shows potential in largescale food and biofuel production. Similar switches have been found in many microalgae and have been exploited in cultivation (e.g., via high-light induction or change of nutritional mode) to improve the productivity of valuable cellular components such as astaxanthin, ketocarotenoid, and a-tocopherol (Ogbonna et al, 1999;Hata et al, 2001;Zhang and Lee, 2001). Nevertheless, the molecular mechanism underlying the switch remains unclear.…”
mentioning
confidence: 69%
“…Such a controlled switch that exploits the advantages of both autotrophy and heterotrophy shows potential in largescale food and biofuel production. Similar switches have been found in many microalgae and have been exploited in cultivation (e.g., via high-light induction or change of nutritional mode) to improve the productivity of valuable cellular components such as astaxanthin, ketocarotenoid, and a-tocopherol (Ogbonna et al, 1999;Hata et al, 2001;Zhang and Lee, 2001). Nevertheless, the molecular mechanism underlying the switch remains unclear.…”
mentioning
confidence: 69%
“…For all the cultures, cell growth rapidly increased during the first 6 d of cultivation but the cells in the fed-batch culture and the two-stage culture continued to grow rapidly until 14 d. It was demonstrated that the two-stage culture strategy was effective in improving astaxanthin production in Chlorococcum sp. and H. pluvialis (28,29). For astaxanthin production in H. pluvialis, the two-stage culture strategy was considered better than the one-stage system and suitable for mass production (30).…”
Section: Resultsmentioning
confidence: 99%
“…nov. (Duckworth et al, 1998), Brevibacterium KY-4313 (Nelis and De Leenheer, 1989), Bradyrhizobium strain ORS278 (Hannibal et al, 2000), and Gordonia jacobaea MV-1 (De Miguel et al, 2000); the halophilic archaeon Haloferax alexandrinus TM T (Asker and Ohta, 2002) and various green micro-algae, including Chlorella pyrenoidosa (Czygan, 1964), Chlorococcum sp. strain MA-1 (Zhang and Lee, 2001), and Chlorella zofingiensis (Li et al, 2006), there is clear potential for employing D. natronolimnaea HS-1 to synthesize canthaxanthin. Table 5 shows a comparative study between microbial sources of canthaxanthin.…”
Section: Validation Of the Optimal Conditions And Modelmentioning
confidence: 99%
“…A similar pattern has also been observed in some other carotenogenic strains such as Phaffia rhodozyma (Vazquez et al, 1997), Chlorococcum sp. (Zhang and Lee, 2001), Rhodotorula mucilaginosa (Aksu and Eren, 2005), Gordonia jacobaea (VeigaCrespo et al, 2005), and Sporobolomyces ruberrimus H110 .…”
Section: Validation Of the Optimal Conditions And Modelmentioning
confidence: 99%
See 1 more Smart Citation